Substitution of Inorganic Fertilizer In SRI Paddy Cultivation Effect on Growth, Production and Soil Organisms: Substitusi Pupuk Kimia pada Budidaya Padi SRI Pengaruhnya Terhadap Pertumbuhan, Produksi dan Organisme Tanah - Kurniawan, Rury; Anas, Iswandi; Widyastuti, Rahayu; Sutandi, Atang (Jurnal Ilmu Tanah dan Lingkungan, 2019)
This research was aimed to study the effect of SRI cultivation compared to conventional methods with different levels of fertilization on the growth and production and to study the activity and populations of soil organisms. System of Rice Intensification (SRI) is an innovation paddy cultivation that still evolving but has been able to increase production. This study was conducted from December 2014 until April 2015 on irrigated land in Pakem district, Sleman regency, D.I Yogyakarta Province. This study used a split-plot design. The main plot is an SRI method and conventional cultivation, and subplots are four levels of fertilization, namely inorganic fertilizer dosage recommendation and as combined with organic fertilizer and bio-organic fertilizer. The results showed plant height, number of tillers, number of productive tillers and grain yield the SRI cultivation was significantly higher than conventional farming. SRI method was able to increase grain yield higher compared with conventional cultivation and the application of inorganic fertilizer combined with bio-organic fertilizer did not differ on the growth and yield and the interaction between the method with the application of fertilizer did not show significant differences. The activity of soil organisms and populations also did not show different. Keywords: Growth, production and soil organism, System of Rice Intensification (SRI)